PENGARUH BIAYA PEMELIHARAAN ALAT-ALAT PRODUKSI TERHADAP HARGA POKOK PRODUKSI (Studi Kasus Pada PT. Unilon Textile Industries) - Apit Yuliman Ermaya; Aditya Achmad Fathony; Nena Harismawati (AKURAT | Jurnal Ilmiah Akuntansi FE UNIBBA, 2016)
The study is titled "The Effect of Maintenance Cost Devices Against Production Cost of Production". Based onthetitle, the issue raisedishow much influence the maintenance costs on the cost of production. This studyaims to determinehow the effect ofthe maintenance costof production equipment against the cost of production. The method usedin this research is descriptive analytical method and verification method, whichaimstodescribeorexplain theactualnature ofthe data and proceed with the proof of the hypothesis the authors. Incollecting the necessary data, the authors conducted field research and library research. Statistical analysis used inthis study wasthe correlation analysis, regressi on analysis, analysis of the coefficient of determination, and hypothesis testing for significance testing using t-test, the period analyzed wasfor 5years from 2008 to 2012. Based onthe research results, as reflected inthe coefficient of determination, found thatthe influence ofthe maintenance costof production equipmentto theconsiderablecost of productionis 69%. Testing the hypothesis with a significance level?=0.0 5and degrees of freedom3, shows thet value (4.6210) is greater thant table (3.1825). This means that the cost of maintenance of the means of production significantly affect the cost of production, especiallyon PT. UNILON Textile Industries.